Industrialization under Medieval Conditions? Global Development after COVID-19 - Wim Naudé (Institute of Labor Economics (IZA), 2020)
Industrialization is vital for inclusive and sustainable global development. The two engines of industrialization â exteuro“ innovation and trade â exteuro“ are in danger of being compromised by the COVID-19 pandemic, under conditions increasingly reminiscent of the medieval world. It comes at a time when innovation had already been stagnating under guild-like corporate concentration and dominance, and the multilateral trade system had been buckling under pressure from a return to mercantilist ideas. The COVID-19 pandemic may cause a permanent reduction in innovation and entrepreneurship and may even bring the 4th industrial revolution (4IR) to a premature end. Hence the post-COVID-19 world may be left with trade as the only engine for industrialization for the foreseeable future. If the global community fails to fix the multilateral trade system, the world may start to resemble the Middle Ages in other, even worse, aspects.
Keywords: F01; F13; L26; L52; O25; O30; 330; industrialization; development; trade; innovation; COVID-19; industrial policy